AGRICULTURAL TOURISM AS ONE OF THE WAYS OF DEVELOPING TOURISM IN ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
The article examines possible ways of developing agricultural tourism in Armenia. Analysing the experience of foreign countries, shows the importance of this sphere in the solution of social and territorial problems. The possible socioeconomic effect of developing of agricultural tourism in Armenia is evaluated.
Keywords: development of agricultural tourism; sustained development; agricultural tourist complex; model of development of agricultural tourism